Heterologous production of caffeic acid in microbial hosts: current status and perspectives - Li, Yuanzi; Li, Jiaxin; Zhang, Miao; Liao, Yonghong; Wang, Fenghuan; Qiao, Mingqiang (Frontiers in Microbiology, 2025)
Caffeic acid, a plant-derived phenolic compound, has attracted much attention in the fields of medicines and cosmetics due to its remarkable physiological activities including antioxidant, anti-inflammation, antibacteria, antivirus and hemostasis. However, traditional plant extraction and chemical synthesis methods exist some problems such as high production costs, low extraction efficiency and environmental pollution. In recent years, the construction of microbial cell factories for the biosynthesis of caffeic acid has attracted much attention due to its potential to offer an efficient and environmentally-friendly alternative for caffeic acid production. This review introduces the caffeic acid biosynthesis pathway first, after which the characteristics of microbial hosts for caffeic acid production are analyzed. Then, the main strategies for caffeic acid production in microbial hosts, including selection and optimization of heterologous enzymes, enhancement of the metabolic flux to caffeic acid, supply and recycling of cofactor, and optimization of the production process, are summarized and discussed. Finally, the future prospects and perspectives of microbial caffeic acid production are discussed. Recent breakthroughs have achieved caffeic acid titers of up to 6.17 g/L, demonstrating the potential of microbial biosynthesis. Future research can focus on the enhancement of metabolic flux to caffeic acid biosynthesis pathway, the development of robust microbial hosts with improved tolerance to caffeic acid and its precursors, and the establishment of cost-effective industrial production processes.